Lichen flora of pamukkale (Hierapolis), Turkey - ÇOBANOĞLU, GÜLŞAH (Asian Network for Scientific Information, 2007)
A list of 82 lichen taxa is reported from Pamukkale (Hierapolis) in the province of Denizli. Sixty four taxa from the study area are new records for the province. Four taxa are new to Turkey: Lecania sylvestris, Lecanora sambuci, Opegrapha herbarum, Peltula patellata. © 2007 Asian Network for Scientific Information.
Keywords: Calcareous; Denizli; Flora; Lichen; Turkey